Representações e poder nas literaturas indígenas : brasileira e colombiana - Polastrini, Leandro Faustino (2023)
ABSTRACT: This research aimed to carry out a comparative study between the indigenous poetics of Brazilian indigenous writers and Colombian indigenous writers, assuming as a proposal to make a comparative literature in which inter, transcultural and social issues are part of the analysis of the literary text. Its specific objectives sought: i) to present an overview of the context of emergence of contemporary indigenous literatures in Brazil and Colombia; ii) to present the effects of writing and schooling for the emergence, from the 20th century onwards, of a genuinely indigenous literature in Brazil and Colombia; iii) discuss, from an interdisciplinary perspective, concepts such as representation, identity and power; iv) analyze the forms of representation and power in Brazilian indigenous literature; and v) analyze the forms of representation and power in Colombian indigenous literature. The following poems were located in the configuration of the research corpus: “Metade cara, metade máscara” (2004), by Eliane Potiguara; "A pescaria do Curumim e outros poemas indígenas" (2015), by Tiago Hakiy; Ay Kakyri “Tama eu moro na cidade” (2018) and “O lugar do saber ancestral” (2021), by Márcia Wayna Kambeba; "Coração na aldeia, pés no mundo" (2018) by Auritha Tabajara; “Danzantes del viento” (2010), by Hugo Jamioy Juagibioy; " Encuentros en los senderos Abya Yala " (2004), "En las hondonadas maternas de la piel Shiinalu’uirua shiirua ataa" (2010) by Vito Apüshana; and “Espíritu de pájaro en pozos del ensueño” (2010), by Fredy Chikangana. In this process, it addresses the emergence of indigenous literature in both countries, pointing out the main factors that contributed to this event, mainly the appropriation of writing beyond its sociocommunicative function, and the prediction of different legal provisions, national and international, recognizing different rights of native peoples. In addition, it sought to situate indigenous literary production in the Americas, especially in Latin America, in recent decades, with a time frame that goes from the 2000s to the present, a context in which it brings to light the facts involved in this process, such as the notes of the researchers of the respective countries. In the established course, it presents the theoretical conceptions that permeate the analysis of the poems selected for study, especially the questions of representation, power and identity, assuming here an interdisciplinary dialogue with studies in the area of philosophy, cultural studies and literature, the example of Pierre Bourdieu , Michael Foucault; Ángel Rama, Stuart Hall, Manuel Castells, Néstor García Canclini, Walter Mignolo; Zilá Bernd, Eurídice Figueiredo, Regina Dalcastagnè, Miguel Rocha Vivas, among others. When analyzing Brazilian and Colombian indigenous poetics, he observes that, among other aspects that guide the representations of identity and power in the respective poetics, ancestry is a central element for contemporary indigenous literature, becoming one of the basic identity markers of this movement, as well as tradition, orality and memory that materialize in different figures of Brazilian and Colombian indigenous poetics.